Effects of dietary live and heat-inactive baker's yeast on growth, gut health, and disease resistance of Nile tilapia under high rearing density. (September 2016) - Ran, Chao; Huang, Lu; Hu, Jun; Tacon, Philippe; He, Suxu; Li, Zhimin; Wang, Yibing; Liu, Zhi; Xu, Li; Yang, Yalin; Zhou, Zhigang
Abstract: In this study, the effects of baker's yeast as probiotics was evaluated in Nile tilapia reared at high density. Juvenile tilapia were distributed to tanks at high density (436 fish/m 3 ) and fed with basal diet (CK) or diets supplemented with live (LY) or heat-inactivated yeast (HIY). Another group of fish reared at low density (218 fish/m 3 ) and fed with basal diet was also included (LowCK). After 8 weeks of feeding, growth, feed utilization, gut microvilli morphology, digestive enzymes, and expressions of hsp70 and inflammation-related cytokines in the intestine were assessed. Intestinal microbiota was investigated using 16S rRNA gene pyrosequencing. Fish were challenged with Aeromonas hydrophila to evaluate disease resistance. High rearing density significantly decreased the growth, feed utilization, microvilli length, and disease resistance of fish (CK versus LowCK). Moreover, the intestinal hsp70 expression was increased in fish reared at high density, supporting a stress condition. Compared to CK group, supplementation of live yeast significantly increased gut microvilli length and trypsin activity, decreased intestinal hsp70 expression, and enhanced resistance of fish against A. hydrophila (reflected by reduced intestinal alkaline phosphatase activity 24 h post infection). The gut microbiota was not markedly influenced by either rearing density or yeast supplementation. Heat-inactivated yeast (HIY) didn't display the beneficial effects observed in LY except an increase in gut trypsin activity, suggesting the importance of yeast viability and thus secretory metabolites of yeast. In conclusion, live baker's yeast may alleviate the negative effects induced by crowding stress, and has the potential to be used as probiotics for tilapia reared at high density. Highlights: High rearing density decreased growth, microvilli length, and disease resistance of Nile tilapia. Live yeast improved gut morphology and hsp70 expression, and enhanced disease resistance of tilapia. Dead yeast didn't show most of the beneficial effects, suggesting the importance of yeast viability. Rearing density and yeast didn't markedly change the intestinal microbiota of tilapia.